Evaluation of the Coaching Training Programme for Improving Employee Performance at PT Pama Persada Nusantara - Warsono Hadi Mulyono; Sujarwo Sujarwo; Yudan Hermawan (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study evaluates the effectiveness of a coaching training program implemented at PT Pama Persada Nusantara using the CIPPO (Context, Input, Process, Product, Outcome) framework. Adopting an evaluative qualitative approach, data were collected over four months through observations, in-depth interviews with 18 purposively selected participants, questionnaires, and document analysis. The findings reveal that the program is well aligned with organizational needs and supported by adequate resources and interactive learning processes. Measurable improvements were identified in participants’ coaching competencies, with average scores increasing from 2.6 to 4.1, alongside high satisfaction levels (4.3/5). Early indications of behavioral change were also observed, as approximately 70% of participants reported applying coaching practices in the workplace, accompanied by modest improvements in team performance indicators. However, the study identifies several limitations, including limited practice duration, reliance on self-reported measures, and the absence of longitudinal evaluation to assess sustained impact. The findings suggest that while the program is effective as a short-term learning intervention, its long-term effectiveness depends on stronger organizational integration and the adoption of technology-enhanced learning approaches. This study contributes by extending the CIPPO model through the incorporation of measurable indicators and highlighting the role of digital tools in supporting continuous professional learning within organizational contexts.